The highly conserved FOXJ1 target CFAP161 is dispensable for motile ciliary function in mouse and Xenopus - Anja Beckers (Nature Portfolio, 2021)
Abstract Cilia are protrusions of the cell surface and composed of hundreds of proteins many of which are evolutionary and functionally well conserved. In cells assembling motile cilia the expression of numerous ciliary components is under the control of the transcription factor FOXJ1. Here, we analyse the evolutionary conserved FOXJ1 target CFAP161 in Xenopus and mouse. In both species Cfap161 expression correlates with the presence of motile cilia and depends on FOXJ1. Tagged CFAP161 localises to the basal bodies of multiciliated cells of the Xenopus larval epidermis, and in mice CFAP161 protein localises to the axoneme. Surprisingly, disruption of the Cfap161 gene in both species did not lead to motile cilia-related phenotypes, which contrasts with the conserved expression in cells carrying motile cilia and high sequence conservation. In mice mutation of Cfap161 stabilised the mutant mRNA making genetic compensation triggered by mRNA decay unlikely. However, genes related to microtubules and cilia, microtubule motor activity and inner dyneins were dysregulated, which might buffer the Cfap161 mutation.